Investigation of the functioning of a vortex tube in supply of disperse flow (gas – dust particles) to the tube - Shaporev, Valery; Pitak, Inna; Pitak, Oleg; Briankin, Serhii (Technology audit and production reserves, 2017)
The process of dry dust removal of exhaust gases from the production of zinc white after melting furnaces of metallic zinc in a vortex tube under aerodynamic conditions is studied, which leads to the occurrence of Rank effect. It is proved that the behavior of the gas-dispersed flow under investigation during flow in a vortex tube is the same as for a gas flow without an aerosol. It is experimentally established that agglomeration of aerosol particles due to high-speed collisions of particles is observed in the vortex tube in the zone of quasi-solid rotation, where the most intense redistribution of energy and temperature is observed. The resulting agglomerates are almost 10 times larger than the dust particles that are fixed at the inlet to the vortex tube. The purification efficiency achieved is 97.8–99.9 %, depending on the gas flow rate at the inlet to the tube. The possibility of catalytic destruction of gas impurities (CO, NOx, SO2) is proved when adding water vapor to the gas flow at the inlet of the tube as a catalyst. The dependence of the vortex tube utilization efficiency as a separator on various factors is studied. It is proved that in the vortex tubes, in comparison with the existing centrifugal cyclone ЦН-11, a significant (up to 6–9 %) increase in the efficiency of fine dust collection in the proposed dust-purification system. This opens up prospects for the introduction of vortex tubes and vortex chambers and helps to reduce the industrial negative impact on the atmosphere.